2000
DOI: 10.1042/0264-6021:3470369
|View full text |Cite
|
Sign up to set email alerts
|

The CB1 cannabinoid receptor is coupled to the activation of protein kinase B/Akt

Abstract: Cannabinoids exert most of their effects in the central nervous system through the CB(1) cannabinoid receptor. This G-protein-coupled receptor has been shown to be functionally coupled to inhibition of adenylate cyclase, modulation of ion channels and activation of extracellular-signal-regulated kinase. Using Chinese hamster ovary cells stably transfected with the CB(1) receptor cDNA we show here that Delta(9)-tetrahydrocannabinol (THC), the major active component of marijuana, induces the activation of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(98 citation statements)
references
References 35 publications
7
91
0
Order By: Relevance
“…4,14 At any rate, of interest is the finding that activation of CB1 (in neuronal cells) or CB2 (in immune cells) receptors prevents AEA-induced apoptosis, 43 a concept that has been extended to different models of programmed cell death. [40][41][42] In the same line, an interesting observation has recently shown that activation of CB1 receptors protects rat glioma cells against HIV-1 Tat-induced cytotoxicity. 45 The relative involvement of cannabinoid and vanilloid receptors in the induction of apoptosis by AEA has been recently investigated also in rat glioma cells, where the proapoptotic effect of AEA through activation of VR1 has been confirmed together with oxidative stress induction and calpain activa-tion.…”
Section: Involvement Of Aea and Congeners In Apoptosismentioning
confidence: 60%
See 1 more Smart Citation
“…4,14 At any rate, of interest is the finding that activation of CB1 (in neuronal cells) or CB2 (in immune cells) receptors prevents AEA-induced apoptosis, 43 a concept that has been extended to different models of programmed cell death. [40][41][42] In the same line, an interesting observation has recently shown that activation of CB1 receptors protects rat glioma cells against HIV-1 Tat-induced cytotoxicity. 45 The relative involvement of cannabinoid and vanilloid receptors in the induction of apoptosis by AEA has been recently investigated also in rat glioma cells, where the proapoptotic effect of AEA through activation of VR1 has been confirmed together with oxidative stress induction and calpain activa-tion.…”
Section: Involvement Of Aea and Congeners In Apoptosismentioning
confidence: 60%
“…39 Besides the modulation of ceramide synthesis and degradation, it has been shown that cannabinoids are able to modulate, again through CB1 receptors, the phosphatidylinositol 3-kinase/ protein kinase B (PI3K/PKB) pathway, which serves as a pivotal antiapoptotic signal. 40,41 This finding is of particular interest, because it points towards a protective role of cannabinoid receptors against programmed cell death, a concept that has found new grounds in human astrocytoma cells. 42 The first demonstration that activation of cannabinoid receptors by AEA had a protective role was reported in human neuroblastoma and lymphoma cells, where AEA was shown to induce apoptosis through vanilloid receptors.…”
Section: Involvement Of Aea and Congeners In Apoptosismentioning
confidence: 99%
“…In the nervous system, endocannabinoids AEA and 2-AG are synthesized and released on demand from membrane-bound phospholipids, and act at presynaptic Gi-coupled CB1 and CB2 receptors [15][16][17][18]. CB1 receptors are localized predominantly to nerve terminals and function to suppress neurotransmitter release and excitotoxic signaling [13,14,[19][20][21][22]. Consequently, promoting cannabinergic signaling by inhibiting endocannabinoid inactivation is a neuroprotective strategy that is being intensively pursued.…”
Section: Introductionmentioning
confidence: 99%
“…This observation was consistent with other reports in which activation of ERK by G i -protein-coupled receptors required the activation of PI3-kinase . Moreover, it has been shown that CB1-R is capable of activating PKB through a PI3-kinase-dependent pathway (Gomez del Pulgar et al, 2000Pulgar et al, , 2002. To test the role of PI3-kinase in the activation of ERK by endocannabinoids in hippocampal slices, we pretreated the slices with a specific inhibitor of this kinase, LY294002 (Vlahos et al, 1994).…”
Section: Endocannabinoids Activate Mek and Erk Independently Of Pi3-kmentioning
confidence: 99%
“…Most of the data were obtained in non-neuronal cell lines, in which stimulation of CB1-Rs activates the extracellular-regulated kinase (ERK) subtype of mitogenactivated protein (MAP) kinases (Bouaboula et al, 1995a;Wartmann et al, 1995), leading to the expression of the immediate-early gene (IEG) Zif268 (also known as egr-1, NGFI-A, or Krox-24) (Bouaboula et al, 1995a). CB1-Rs are also coupled to the activation of protein kinase B/Akt (PKB) through the phosphatidylinositol 3 (PI3)-kinase pathway (Gomez del Pulgar et al, 2000Pulgar et al, , 2002. Little is known about the signaling pathways regulated by cannabinoids in the adult nervous system.…”
Section: Introductionmentioning
confidence: 99%